Aspen Plus simulation of a low capacity organic Rankine cycle heated by solar energy - S.M. Shalaby (Elsevier, 2022)
In this work, the performance of the organic Rankine cycle (ORC) of 1 kW output power was studied using Aspen Plus software simulation. In order to improve the performance of the ORC, eight organic fluids were tested as working fluid. The operational parameters such as working temperature, pressure and flow rates were also optimized. The results showed that the optimal performance of the ORC was obtained when hexane was used as working fluid with mass flow rate of 36 kg/hr, with working pressure of 11.5 bar and at a temperature of 173 °C. A parabolic trough solar collector was designed using the system advisor model software to provide the required input heat of the power cycle considering only the top five efficient working fluid: hexane, toluene, R123, R11, and R245fa.